2006
DOI: 10.1007/s10692-006-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of heterogeneous cellulose—solvent systems

Abstract: The effect of low-molecular-weight liquids on the physicochemical properties of cellulose was investigated, the mechanical and chemical effects on the structure of cellulose were compared, and the reactivity of cellulose was investigated. The determining role of the system of hydrogen bonds and its structure in the reactivity of cellulose, which can be varied with chemical or mechanical effects, was demonstrated.Cellulose processing technology based on formation of cellulose ethers includes processes that take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Now, we have to figure out the specificity, if any, of the CMC−Si interaction, and how it allows the conservation of the electrode texture and electrical wiring despite repeated breath and consequent back and forth changes in volume. Owing to the presence of polar groups, it is well documented that carbohydrates-based polymers undergo many inter- and intrachain hydrogen interactions , and that the extent and dynamic of interactions with the polar surface depend on the presence of water or mechanical stress . Various substitution of the OH groups can be applied in order to modify the nature and strength of these interactions, as suggested by Hochgatterer et al In order to obtain a better understanding of the nature of the interaction and behavior with respect to the Si−Li reaction, several approaches have been pursued enlisting modifications of (1) the polymer and (2) the Si surface.…”
Section: Resultsmentioning
confidence: 99%
“…Now, we have to figure out the specificity, if any, of the CMC−Si interaction, and how it allows the conservation of the electrode texture and electrical wiring despite repeated breath and consequent back and forth changes in volume. Owing to the presence of polar groups, it is well documented that carbohydrates-based polymers undergo many inter- and intrachain hydrogen interactions , and that the extent and dynamic of interactions with the polar surface depend on the presence of water or mechanical stress . Various substitution of the OH groups can be applied in order to modify the nature and strength of these interactions, as suggested by Hochgatterer et al In order to obtain a better understanding of the nature of the interaction and behavior with respect to the Si−Li reaction, several approaches have been pursued enlisting modifications of (1) the polymer and (2) the Si surface.…”
Section: Resultsmentioning
confidence: 99%
“…28 Generally, depending on the presence of water and mechanical stress, polymeric carbohydrates undergo various inter-and intra-chain interactions forming hydrogen bonds due to the numerous polar groups in their structure. [29][30][31] Thermal stability of Na CMC is strongly dependent on its dissociation degree and the presence of intraand intermolecular bonding. 32 This would explain why the thermal properties of individual electrode components with the electrolyte are different from those of the composite electrode when in contact with the same electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the presence of polar groups, it is well-demonstrated that cellulose-based polymers undergo many inter- and intrachain hydrogen-bonding interactions. , Larcher et al suggested that hydrogen bonding enables a self-healing effect, which consequently preserves the electronic conductive path within the Si-based electrodes . This result manifests the importance of robust polymer chain networks constructed within the electrode.…”
Section: Establishing Mechanically Robust Electrodesmentioning
confidence: 99%